Methanol and ethanol oxidation on carbon supported nanostructured Cu core Pt–Pd shell electrocatalysts synthesized via redox displacement - Sieben, Juan Manuel (2014)
Six different carbon-supported Cu core Pt–Pd shell (Cu@Pt–Pd) catalysts have been successfully synthesized by the galvanic replacement of Cu atoms by Pt4+ and Pd2+ ions at room temperature and their electrocatalytic activity for methanol and ethanol oxidation have been evaluated in acid media. Cu@Pt–Pd core shell nanoparticles with a narrow size distribution and an average diameter in the range of 3.1–3.5 nm were generated onto the carbon support. The compositional and the structural analysis of the as-prepared materials pointed out that the nanoparticles are formed by a Cu rich core covered by a Pt–Pd rich shell due to the interdiffusion of the metals after the galvanic replacement reaction. The electrocatalytic properties of the Cu@Pt–Pd electrodes in the electro-oxidation of methanol and ethanol was found to be dependent on the electrochemical surface area, lattice strain of the surface, composition and thickness of the Pt–Pd shell surrounding the Cu core. The optimum catalyst composition to obtain the best performance for methanol and ethanol electro-oxidation was determined to be Pt0.59Pd0.324Cu0.167/C (6.2 wt.% Pt, 2.2 wt.% Pd and 0.7 wt.% Cu). This catalyst has a greatly enhanced mass activity, lower onset potential and poisoning rate, and higher turnover number in the MOR and EOR reactions compared to a commercial Pt0.51Ru0.49/C (20 wt.% Pt and 10 wt.% Ru). Consequently, this simple preparation method is a viable approach to making a highly active catalyst with low platinum content for application in direct alcohol fuel cells (DAFCs).